Analisis dampak peraturan pemerintah desain besar olahraga Nasional (DBON) terhadap perkembangan olahraga bulu tangkis - Habibie, Muhammad; Fitrianto, Ari Tri; Fauzi, Ahmat (Universitas Hamzanwadi, 2023)
Interest in exercising in the community in this era of globalization is not only to be healthy but as a place to achieve the name of the region. The purpose of this study is to find out data about the relevance of dbon policies to field managers, increasing the number of badminton sports entrants, badminton sports building facilities and increasing the achievements of clubs / agencies practicing on the field after there are dbon regulations. The research method used by researchers is descriptive quantitative. The population in this study were all badminton GORs in Banjarmasin. researchers will use non probability sampling techniques. samples taken as many as 16 badminton GORs in Banjarmasin. Data collection techniques using questionnaires. Questionnaire. Based on the results of the impact of government regulations on the development of badminton sports in the Banjarmasin area, the relevance indicator has a percentage of 14.3%, increased visitors have a percentage of 16.5%, increased facilities have a percentage of 20.3% and increased achievement has a percentage of 13%. The result of the analysis of sports buildings in the Banjarmasin area based on these 4 indicators is 64.1%. concluded that there is an impact of the national sports grand design government regulation on the development of badminton sports in the Banjarmasin area.